Bayesian averaging for ground state masses of atomic nuclei in a Machine Learning approach - Mumpower, Matthew; Li, Mengke; Sprouse, Trevor M.; Meyer, Bradley S.; Lovell, Amy E.; Mohan, Arvind T. (Frontiers in Physics, 2023)
We present global predictions of the ground state mass of atomic nuclei based on a novel Machine Learning (ML) algorithm. We combine precision nuclear experimental measurements together with theoretical predictions of unmeasured nuclei. This hybrid data set is used to train a probabilistic neural network. In addition to training on this data, a physics-based loss function is employed to help refine the solutions. The resultant Bayesian averaged predictions have excellent performance compared to the testing set and come with well-quantified uncertainties which are critical for contemporary scientific applications. We assess extrapolations of the model's predictions and estimate the growth of uncertainties in the region far from measurements.